AN ANALYSIS OF STUDENTS’ EQUIVALENCE IN TRANSLATING ENGLISH NARRATIVE TEXT INTO BAHASA INDONESIA AT ENGLISH STUDY PROGRAM OF ISLAMIC UNIVERSITY OF INDRAGIRI - Samlah; Agus Mustajib; Edi Ardian (J-Shelves of Indragiri (JSI), 2024)
The objective of the research was to find out and describe the students’ narrative text equivalence, to find out the equivalence level of students’ translation, and to figure out the students’ difficulties in translating and their solution to overcome the problem. The population of the research was a sixth semester students’ of English study program, while the participant was 14 students. The study used a descriptive qualitative method with the instruments is test. The research findings showed that 52.5% of students’ translation exceeded the ‘average’ standard, it was dynamic equivalence translation with almost half of participant did that. Then, the second highest category was formal equivalence with the total 34.4% or at the ‘low’ standard. In the last, students’ translate non-equivalence with the total 7.2%, or at ‘very low’ standard. Meanwhile, the research finding showed that there were two primary difficulties faced by the students: difficulty to understand the meaning of the text and difficulty finding the most equivalent meaning in bahasa. To overcome those problems, they used a guessing strategy to understand the meaning of the sentence. Overall, it can be concluded that the equivalence of the translation narrative text English into Indonesia by the sixth semester students of English study program was fair.